2004
DOI: 10.1074/jbc.m313850200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Interaction between High Molecular Mass Kininogen and the Urokinase Plasminogen Activator Receptor

Abstract: The urokinase plasminogen activator receptor (uPAR) is a multifunctional, GPI-linked receptor that modulates cell adhesion/migration and fibrinolysis. We mapped the interaction sites between soluble uPAR (su-PAR) and high molecular mass kininogen (HK). Binding of biotin-HK to suPAR was inhibited by HK, 56HKa, and 46HKa with an IC 50 of 60, 110, and 8 nM, respectively. We identified two suPAR-binding sites, a higher affinity site in the light chain of HK and 46HKa (His 477 -Gly 496 ) and a lower affinity site w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 30 publications
2
50
0
Order By: Relevance
“…Overlapping peptides (LRG20, YLP20, and PGS20) from uPAR domain 2 (amino acids 144 -173) blocked ScuPAinduced expression of pERK1/2 (P Ͻ 0.003; Fig. 3, C and F, and Table 1) (50). A corresponding scrambled peptide (PGS20) had no effect.…”
Section: Scupa Stimulates Perk1/2 and Pakt (Sermentioning
confidence: 95%
See 3 more Smart Citations
“…Overlapping peptides (LRG20, YLP20, and PGS20) from uPAR domain 2 (amino acids 144 -173) blocked ScuPAinduced expression of pERK1/2 (P Ͻ 0.003; Fig. 3, C and F, and Table 1) (50). A corresponding scrambled peptide (PGS20) had no effect.…”
Section: Scupa Stimulates Perk1/2 and Pakt (Sermentioning
confidence: 95%
“…Angiogenesis microscopic images were obtained using a Nikon TE200 microscope with a ϫ20/0.45 lens. (50). The modeling was performed with the Cn3D4.3 program available from the National Center for Biotechnology Information structure website.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies indicated that HK did not bind to urokinase plasminogen activator receptor (uPAR) (41), emerging evidence suggests that the unique regions of HK might serve as urokinase-binding sites (45). Recently, it has been reported that both HK and cleaved HK bound to gC1qR, cytokeratin 1 and the soluble extracellular form of urokinase plasminogen activator receptor (uPAR) (46).…”
Section: Discussionmentioning
confidence: 99%